Umetnostna izrazna sredstva v socialnem delu - Kustec, Klavdija (Socialno delo, 2011)
The paper presents a summarised historical development and use of artistic means of expression in diverse fields of work with people. It gives a short description of predominant models or approaches - the medical and the social model - and within this context paradigmatic shifts in social work, which are important for work with artistic means, are shown. Special attention is devoted to successfulness or effectiveness of work with artistic means of expression and to required competences of social workers who use artistic means of expression in their work.
Keywords: umetnostniško izražanje; psihosocialna podpora; social work; socialno delo